Anticardiolipin and other antiphospholipid antibodies in critically ill COVID-19 positive and negative patients. Issue 9 (26th April 2021) - Trahtemberg, Uriel; Rottapel, Robert; Dos Santos, Claudia C; Slutsky, Arthur S; Baker, Andrew; Fritzler, Marvin J
Abstract : Background: Reports of severe COVID-19 being associated with thrombosis, antiphospholipid antibodies (APLA), and antiphospholipid syndrome have yielded disparate conclusions. Studies comparing patients with COVID-19 with contemporaneous controls of similar severity are lacking. Methods: 22 COVID-19 + and 20 COVID-19 – patients with respiratory failure admitted to intensive care were studied longitudinally. Demographic and clinical data were obtained from the day of admission. APLA testing included anticardiolipin (aCL), anti-β2glycoprotien 1 (β2GP1), antidomain 1 β2GP1 and antiphosphatidyl serine/prothrombin complex. Antinuclear antibodies (ANAs) were detected by immunofluorescence and antibodies to cytokines by a commercially available multiplexed array. Analysis of variance was used for continuous variables and Fisher's exact test was used for categorical variables with α=0.05 and the false discovery rate at q=0.05. Results: APLAs were predominantly IgG aCL (48%), followed by IgM (21%) in all patients, with a tendency towards higher frequency among the COVID-19 + . aCL was not associated with surrogate markers of thrombosis but IgG aCL was strongly associated with worse disease severity and higher ANA titres regardless of COVID-19 status. An association between aCL and anticytokine autoantibodies tended to be higher among the COVID-19 + . Conclusions: Positive APLA serology was associated with more severe disease regardless of COVID-19 status. Trial registration number: NCT04747782